2008 7th International Pipeline Conference, Volume 3 2008
DOI: 10.1115/ipc2008-64277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crack Tip Constraint Effects on the Assessment of Pipes Subjected to Combined Loading Conditions

Abstract: Under certain conditions, pipelines may be submitted to biaxial loading situations. In these cases, questions arise about how biaxial loading influence the driving force (i.e.: CTOD, J-integral) of possible presented cracks and how affects the material fracture toughness. For further understanding of biaxial loading effects on fracture mechanics behavior of cracked pipelines, this work presents a numerical analysis of crack-tip constraint of circumferentially surface cracked pipes and SENT specimens using full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…6(d)) was used to describe the shape of the crack tip, the radius of which was equal to the element size of the crack front. This kind of structure has been proven to have a good effect in simulating the blunting process of crack tips, and the simulation results are in good agreement with the test results (Cravero et al, 2008;Østby et al, 2008).…”
Section: Fea Modelsupporting
confidence: 68%
“…6(d)) was used to describe the shape of the crack tip, the radius of which was equal to the element size of the crack front. This kind of structure has been proven to have a good effect in simulating the blunting process of crack tips, and the simulation results are in good agreement with the test results (Cravero et al, 2008;Østby et al, 2008).…”
Section: Fea Modelsupporting
confidence: 68%
“…Due to symmetry, the 1/4 of the specimen which meshed by eight-node reduced integration unit (C3D8R) was modeled. The element size in the crack growth zone in this paper is 0.125mm [7,8]. The transition from a coarse mesh away from the crack tip region to a fine mesh in the crack tip region is obtained by using a structured transitional mesh pattern.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…They showed that clamped SE(T) specimens having crack sizes in the range 0.2 ≤ a/W ≤ 0.4 provide fracture resistance curves in good agreement with the corresponding fracture behavior of circumferentially cracked pipes. Also a number of previous works[15,16,113,[115][116][117][118][119] have addressed effects of constraint on ductile crack growth in SE(T) fracture specimens and cracked pipelines to establish a more effective correlation of fracture behavior for these crack configurations. CTOD resistance curves derived from multiple methods were experimentally investigated for low and high strain hardening material to show the sensivity of the CTOD values on the deriving method, such J-CTOD relationships and DCG[120].…”
mentioning
confidence: 99%